The use of microgravity technique in archaeology: A case study from the St. Nicolas Church in Pukanec, Slovakia - PÁNISOVÁ, Jaroslava; PAŠTEKA, Roman (Contributions to Geophysics and Geodesy, 2009)
The detection of subsurface cavities, such as crypts, cellars and tunnels, in churches and castles belongs to successful applications of the employment of surface gravity measurement techniques in archaeo-prospecting. The old historic building exploration requires using of non-invasive methods, and hence the microgravity technique is a proper candidate for this task. On a case study from the Roman-Catholic Church of St. Nicolas in the town Pukanec the results of using microgravity for detection and delineation of local density variations caused by a near-surface void are shown. The acquired negative anomaly in the residual Bouguer anomalies ﬁeld suggested the presence of a possible void feature. Euler deconvolution and 3D modelling were used to estimate the depth and shape of the anomalous source. Additionally, measurements of the vertical gravity gradient on several stations were performed. We tested how the use of a downward continuation of gravity, utilizing the real vertical gravity gradient, inﬂuences the shape and amplitude of the ﬁnal Bouguer anomaly map.